The effect of solvents on the Soxhlet extraction of omega 3 from perah oil - Hadi Tan, Nuraimi Azlan (Penerbit UTM Press, 2014)
This study aims to investigate the influence of solvent on the Soxhlet extraction of omega 3 in perah seed oil. Three types of extraction solvent include hexane, hexane: methanol (90:10) and methanol: ethanol (70:30) were investigated. The concentration of extracted omega 3 was measured using Gas chromatography (GC), the colour of extracted oil was classified using colormeter and the total phenolic content (TPC) by Folin-Ciocalteau colorimetry. Based on the total yield extraction of the oil, the result shows that hexane solvent (57.5%) shows better performance compared to hexane-methanol (53.42%) and ethanol-methanol (34.52%). For the omega 3 concentration, hexane-methanol solvent provided highest yield at 1.41g ω-3/g oil followed by ethanol-methanol and hexane at 1.32 ω-3/g oil and 1.15 ω-3/g oil respectively. On the other hand, the extracted oil using hexane as extraction solvent was appeared to be lighter in colour as compared to other solvents studied. In addition, total phenolics content of perah oil was high with hexane solvent. As conclusion, the polar solvent of methanol and ethanol promoted the extraction of omega 3; however, it may cause a darker appearance of the extract as well as reducing the content of phenolic compounds.